Some questions as regards the crime of association disloyal administration in Spain, especially responsibility and omission (2014)
This article addressed some dogmatic issues related with the crime of corporate unfair management (art. 295 of the Spanish Penal Code). In addition, a brief mention is made about the future crime of unfair management which is part of the reform of the Pen